Pemahaman Asma’ dan Sifat Allah Dalam Kitab I‘Tiqad A’immah Ahlil Hadits: Telaah Metodologi Ahli Hadis dan Relevansinya Terhadap Krisis Spiritualitas di Era Teknologi Modern - Nurhidayah; M. Farid Zaini (Pendidikan Agama Islam, 2025)
The development of modern technology, including artificial intelligence (AI), has had a major impact on human lifestyles and ways of thinking. Excessive dependence on technology often gives rise to secularism, hedonism, and even spiritual crises, which ultimately lead to a weakening of understanding of the concept of monotheism. In this context, strengthening faith becomes very important, one of which is through a correct understanding of the names and attributes of Allah. This study focuses on the responses and methods of Hadith scholars in understanding and interpreting the names and attributes of Allah as an effort to maintain the purity of faith amid the challenges of modernity. Hadith scholars are known to be cautious and moderate in determining the attributes of Allah,adhering strictly to the text without distorting the meaning or rejecting attributes. The research method used is library research, referring to various classical creed books and relevant journals. The main source of analysis is the book I‘tiqad A’immah Ahlil Hadith by Abu Bakar al-Isma‘ili, which represents the basic principles of the creed of the Hadith Scholars. The results of the research show that the Hadith Scholars emphasise the acceptance of the attributes of Allah as they are, without deviating interpretations and without likening Allah to His creatures. This finding confirms that the Ahli Hadith method is not only relevant in maintaining the purity of creed, but can also be a spiritual solution for modern humans facing a crisis of divinity due to the dominance of technology and secular views of life.